First evaluation of the Behavioral Addiction Indoor Tanning Screener (BAITS) in a nationwide representative sample. (14th December 2017) - Diehl, K.; Görig, T.; Breitbart, E.W.; Greinert, R.; Hillhouse, J.J.; Stapleton, J.L.; Schneider, S.
Summary: Background: Evidence suggests that indoor tanning may have addictive properties. However, many instruments for measuring indoor tanning addiction show poor validity and reliability. Recently, a new instrument, the Behavioral Addiction Indoor Tanning Screener (BAITS), has been developed. Objectives: To test the validity and reliability of the BAITS by using a multimethod approach. Methods: We used data from the first wave of the National Cancer Aid Monitoring on Sunbed Use, which included a cognitive pretest (August 2015) and a Germany‐wide representative survey (October to December 2015). In the cognitive pretest 10 users of tanning beds were interviewed and 3000 individuals aged 14–45 years were included in the representative survey. Potential symptoms of indoor tanning addiction were measured using the BAITS, a brief screening survey with seven items (answer categories: yes vs. no). Criterion validity was assessed by comparing the results of BAITS with usage parameters. Additionally, we tested internal consistency and construct validity. Results: A total of 19·7% of current and 1·8% of former indoor tanning users were screened positive for symptoms of a potential indoor tanning addiction. We found significant associations between usage parameters and the BAITS (criterion validity). Internal consistency (reliability) was good (Kuder–Richardson‐20, 0·854). The BAITS was shown to be a homogeneous construct (construct validity). Conclusions: Compared with other short instruments measuring symptoms of a potential indoor tanning addiction, the BAITS seems to be a valid and reliable tool. With its short length and the binary items the BAITS is easy to use in large surveys. Abstract : What's already known about this topic? Ultraviolet radiation has been classified as carcinogenic to humans and an important source of exposure is indoor tanning facilities. A growing body of research has provided preliminarily support for viewing excessive tanning as a behaviour with addictive potential. Different screening instruments for indoor tanning addiction exist but concerns about their internal consistency as well as internal and external validity have been raised. What does this study add? We tested the validity and reliability of the recently developed Behavioral Addiction Indoor Tanning Screener (BAITS). Compared with other short instruments measuring symptoms of a potential indoor tanning addiction, the BAITS seems to be a valid and reliable tool. With its short length and binary items the BAITS is easy to use in large surveys. What are the clinical implications of this work? The BAITS seems to be a quick, valid and reliable tool for identifying symptoms of a potential addiction to indoor tanning. It may help physicians and healthcare providers to identify individuals in need of specific counselling to deal with this problem. Plain language summary available online Respond to this article